Importance Of Practical Life Activity For The Development Of Self-Regulation Skills In Children Aged 4-5 Years - Efri Manda Sari Hasibuan (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to describe the utilization of practical life activities for the development of regulation skills of children aged 4-5 years. whether the habituation method can improve self-regulation skills in students at RA Qurratu a'ayun, Deli Tua District, Deli Serdang Regency. The research was conducted using classroom action research method developed by Kemmis and Taggart. The provision of action is carried out in 2 cycles, each cycle consists of 4 stages, namely planning, action, observation, and reflection and each cycle takes place within two days. The data generated were then analyzed in quantitative and qualitative ways. Based on the analysis of quantitative data, this class action research was able to improve the ability of self-regulation, from pre-cycle to cycle two by 70%. As for qualitatively, Practical Life activity with activities in the form of learning while playing with loose part media and blocks provided and then cleaning up the toys to their original place, and equipped with singing and reward methods, is able to improve children's regulation skills, so that they are able to control emotions by sharing and queuing in using toys and getting used to cleaning up toys back to their original place after use.